Signal transduction in Plasmodium-Red Blood Cells interactions and in cytoadherence - Cruz,Laura N. (2012)
Malaria is responsible for more than 1.5 million deaths each year, especially among children (Snow et al. 2005). Despite of the severity of malaria situation and great effort to the development of new drug targets (Yuan et al. 2011) there is still a relative low investment toward antimalarial drugs. Briefly there are targets classes of antimalarial drugs currently being tested including: kinases, proteases, ion channel of GPCR, nuclear receptor, among others (Gamo et al. 2010). Here we review malaria signal transduction pathways in Red Blood Cells (RBC) as well as infected RBCs and endothelial cells interactions, namely cytoadherence. The last process is thought to play an important role in the pathogenesis of severe malaria. The molecules displayed on the surface of both infected erythrocytes (IE) and vascular endothelial cells (EC) exert themselves as important mediators in cytoadherence, in that they not only induce structural and metabolic changes on both sides, but also trigger multiple signal transduction processes, leading to alteration of gene expression, with the balance between positive and negative regulation determining endothelial pathology during a malaria infection.